Etika Utilitarianisme Jeremy Bentham Sebagai Basis Posisi Etis Ekonomi Pancasila Di Indonesia - Putra, Trassanda Scudetto Widestomo (Economie: Jurnal Ilmu Ekonomi, 2024)
The ethics in the implementation of economic policies emphasize the direction of justice, goodness, as well as knowing what should and should not be done in an economic activity involving all humans within it (Akhsan, 2020). This research aims to explore the issues of ideas and the implementation of Pancasila Economics adopted in the economic life of the Republic of Indonesia. The analysis of Pancasila Economics is based on the principles of utilitarian ethics derived from the thoughts of Jeremy Bentham (1748-1832). The research problem is formulated as how the ethical position of Pancasila Economics in Indonesia is in the analysis of Jeremy Bentham's utilitarian ethics. This study aims to explore the ethical position of Pancasila Economics based on utilitarian ethics principles within the framework of ideas and implementation. The method to achieve these goals and answer the issues is cross-sectional with a qualitative approach. The results of this research indicate a disparity in the ethical position of Pancasila Economics as an idea/concept compared to its implementation in economic policies in Indonesia.